PENGARUH PELATIHAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI - Endarwita Endarwita (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2017)
This study was intended to see how the influence of Training and WorkMotivation toward Employee Job Performance at Bappeda in West Pasaman. The population in this study were all employees at Bappeda in West Pasaman with sample of 53 people, where sampling techniques using saturated sampling. From the result of this study, the training variables (X1) and work motivation (X2) significantly affected the performance (Y) with a significant level of 0.000. The magnitude of the effect of training (X1) and work motivation (X2) on the Performance (Y) is 0.573 (R2 = 57.3). Keywords: Training, Work Motivation, Performance